2020
DOI: 10.1532/hsf.3011
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Postoperative Covid-19 Infection After Cardiac Surgery: Lessons Learned

Abstract: While the focus of the medical community is on the management of COVID-19 and its associated complex presentations, it is critical to recognize that patients will continue to present with other medical problems that require urgent therapeutic interventions. There is growing concern that such interventions might have an impact on the natural history of COVID-19. We present a case of a patient who presented with unstable angina and multivessel coronary artery disease for which coronary artery bypass surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 1 publication
0
29
0
4
Order By: Relevance
“…Patients with COVID-19 disease who undergo surgery suffer a complicated postoperative course [ 5 , 6 ]. Studies have shown that up to 51.2% of these patients had pulmonary complications and among patients who had pulmonary complications after surgery 30-day mortality rate was 38% [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with COVID-19 disease who undergo surgery suffer a complicated postoperative course [ 5 , 6 ]. Studies have shown that up to 51.2% of these patients had pulmonary complications and among patients who had pulmonary complications after surgery 30-day mortality rate was 38% [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cardiac surgery with CPB may cause serious complications in patients with viral interstitial pneumonia, and a few cases of COVID-19 patients with fatal outcome have been published. 3 It is acknowledged that major surgery and aorta cross-clamping exacerbate systemic inflammatory response to surgical trauma by several pathways that can contribute to the deterioration of the postoperative pulmonary function. 4 After reperfusion, the leukocytes' activation and the cytokines' release 5 could result in alveolar injuries through an increased endothelial permeability.…”
Section: Discussionmentioning
confidence: 99%
“…One of the reported cases was diagnosed to have COVID-19 pneumonia after testing of the bronchopulmonary lavage. 2 Coagulation abnormality and thrombosis was noted in another patient. 3 When a postoperative patient tests positive from COVID-19, the management starts immediate shifting of the patient to the COVID-19 care unit of the hospital or to an isolation area.…”
mentioning
confidence: 88%